2018
DOI: 10.3389/fimmu.2018.01689
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis in Autoimmune Diabetes Is Correlated With Poor Glycemic Control and Increased Interleukin-6: A Pilot Study

Abstract: Intestinal dysbiosis associated with immunological deregulation, leaky gut, bacterial translocation, and systemic inflammation has been associated with autoimmune diseases, such as type 1 diabetes (T1D). The aim of this study was to investigate the intestinal dysbiosis in T1D patients and correlate these results with clinical parameters and cytokines. The present study was approved by the Barretos Cancer Hospital (Process number 903/2014), and all participants have signed the informed consent in accordance wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 49 publications
2
55
0
2
Order By: Relevance
“…Intestinal dysbiosis associated with immunological deregulation, leaky gut, bacterial translocation and systemic inflammation has been associated with autoimmune diseases (73) . The innate immune system is composed of a network of cells including neutrophils, natural killer and natural killer T cells, monocytes/macrophages and dendritic cells that mediate the earliest interactions with pathogens (74) .…”
mentioning
confidence: 99%
“…Intestinal dysbiosis associated with immunological deregulation, leaky gut, bacterial translocation and systemic inflammation has been associated with autoimmune diseases (73) . The innate immune system is composed of a network of cells including neutrophils, natural killer and natural killer T cells, monocytes/macrophages and dendritic cells that mediate the earliest interactions with pathogens (74) .…”
mentioning
confidence: 99%
“…A β -diversity represents the dissimilarity between the two gut communities. A total of six studies in this review have analysed the β -diversity of gut microflora, and four of them consistently identified that the gut microbiome of T1D patients showed a remarkably distinct pattern of clustering when compared with that of HCs [ 22 , 24 , 25 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, three studies consistently revealed that Bacteroides positively correlated with the development of T1D [ 24 , 26 , 30 ]. Several species belonging to Bacteroides , including Bacteroides vulgatus , Bacteroides rodentium , and Bacteroides xylanisolvens , were also significantly higher in T1D patients than in HCs [ 22 ]. Similarly, the abundance of Ruminococcus also showed an increasing trend in T1D patients [ 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is seemingly innocuous in healthy individuals, as Bacteroidetes and Firmicutes constitute over 90% of healthy gut microbial assemblage [16]. However, it has been demonstrated that the B. dorei proportion in the gut microbiota is responsible for a variety of diseases, including autoimmune type 1 diabetes mellitus [9,[17][18][19][20][21][22], colorectal diseases [23][24][25][26], atherosclerotic diseases [27][28][29][30], and even Parkinson's disease [31]. On the other hand, there is almost no report regarding B. dorei as a cause of infectious diseases or even a part of its contagious process, which consists of tissue invasion, multiplication and colonisation and in iction of host tissue damage by cytotoxic materials or direct interactions.…”
Section: Discussionmentioning
confidence: 99%